Experimental investigation of photovoltaic thermal solar air collector with exergy performance comparison - Bahtiar Bahtiar; Muhammad Zohri; Ahmad Fudholi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The integration of photovoltaic technology and solar air collector is named a photovoltaic thermal (PVT) system. PVT system generates electricity as pumping power to fan DC and produces thermal energy together with to cooling PV panel. The experimental with the indoor and outdoor evaluation of PVT solar air collector have been compared at the chosen solar intensity of 820 W/m2. The mass flow rate is range from 0.01 kg/s to 0.05 kg/s. The exergy and efficiency exergy accuracy of PVT solar air collector between indoor and outdoor evaluation are 98.42%, 98.11% respectively. The exergy and exergy efficiency comparison results indicated that the indoor and outdoor investigation is suitable.